TECHNOLOGY OF CREATION AND RECOGNITION OF QR CODES AS AN EFFICIENT INSTRUMENT FOR IMPROVING EDUCATIONAL ACHIEVEMENTS OF STUDENT YOUTH ﻿ - T. Bondarenko; P. Tychyna (Kherson State University, 2019)
The technology of creating and recognizing QR codes has been widely used in domestic business, marketing, social projects, and has become an innovative tool for disseminating and retrieving information in the educational environment. The article analyzes the degree of study of QR codes in the scientific literature, identifies historical features, uses, highlights the content of information encoding, points out the difference between static and dynamic submission of output data, examines the forms of organization of learning activities using two-dimensional bar codes, and also describes and presents examples of the use of this tool in the educational process by teachers of higher education institutions. The survey found that students have experience in using QR-codes in the banking or tourism sector as an opportunity to obtain comprehensive information about goods and services. Unfortunately, only 9% of respondents used QR codes in their educational activities. The pedagogical purpose of using the technology of QR-codes is determined by the possibility of implementing intensive forms and methods of vocational training, increasing the motivation of educational activities through the use of modern means of reading, processing, reproduction of information, raising the level of theoretical basis of perception of the data, formation of skills to implement various forms of independent activity in collecting and processing the necessary content. In the process of pedagogical experiment, which was conducted among the students of the direction of training «014.09 Secondary education. Informatics» Pavlo Tychyna Uman State Pedagogical University found that the technology of using QR-codes have sufficient potential during the activation of educational activities, allowing to increase the level of professional competences of the future teacher of informatics, ensuring the efficiency and quality of the educational process.